PENGARUH DISIPLIN KERJA DAN PENGAWASAN TERHADAP KINERJA KARYAWAN PADA PT. KURABO MANUNGGAL TEXTILE INDUSTRIES KOTA TANGERANG - Nuraeni, Leni; Juanda, Angga (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of Work Discipline and Supervision on Employee Performance at PT. Kurabo Manunggal Textile Industries, Tangerang City, either partially or simultaneously. The research method uses quantitative research methods with a descriptive associative approach. The sampling technique used the Slovin formula and a sample of 84 respondents was obtained in this study. The analysis uses validity tests, reliability tests, classical assumption tests, linear regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research are that work discipline has a significant effect on employee performance with the regression equation Y=15.979+0.659X1. The correlation coefficient value is 0.789, meaning that the two variables have a strong level of relationship. The coefficient of determination value is 62.2%. Hypothesis testing obtained a value of tcount > ttable or (11.617 > 1.989). Thus, H0 is rejected and H1 is accepted, meaning that there is a partial positive and significant influence between the Work Discipline variable on employee performance. Supervision has a significant effect on employee performance with the regression equation Y=18.132+0.606X2. The correlation coefficient value is 0.711, meaning that the two variables have a very strong level of relationship. The coefficient of determination value is 50.6%. Hypothesis testing obtained a value of tcount > ttable or (9.160 > 1.989). Thus, H0 is rejected and H2 is accepted, meaning that there is a partial positive and significant influence between the Supervision variables on Employee Performance. Work Discipline and Supervision have a significant effect on employee performance with the regression equation Y=13.605+ 0.492X1+0.222X2. The correlation coefficient value is 0.806, meaning that the independent and dependent variables have a very strong level of relationship. The coefficient of determination value is 65.0%%. Hypothesis testing obtained a value of Fcount > Ftable or (75.348 > 3.11). Thus, H0 is rejected and H3 is accepted, meaning that there is a simultaneous and significant influence between the Work Discipline and Supervision variables on Employee Performance at PT. Kurabo Manunggal Textile Industries, Tangerang City.